Memaksimalkan Keputusan Pembelian melalui Peningkatan Persepsi Harga, Kualitas Produk, dan Keragaman Produk (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Purchasing decisions shown by consumers indicate that the company is able to provide products according to their expectations. Building purchasing decisions is very important to do so that the company can continue to run its business. This study was conducted as an effort to determine the role of price perception, product quality, and product diversity in increasing purchasing decisions at Dewata Vapor, Batuan Branch. The number of samples used as a data source was 90 consumers. Data analysis of the study was carried out using the multiple linear regression method. The results of the test showed that the role of price perception, product quality, and product diversity played a positive and significant role in increasing purchasing decisions at Dewata Vapor, Batuan Branch. The suggestion given based on the results of the study is to continue to improve price perception, product quality, and product diversity so that consumer purchasing decisions can be improved.